A pilot study evaluating a new low-volume colon cleansing procedure for capsule colonoscopy - Hartmann, Dirk; Jakobs, Ralf; Riemann, Jürgen F. (Endoscopy, 2012)
Background and study aims: Colon capsule endoscopy (CCE) offers an alternative approach for endoscopic visualization of the colon. Some of the current CCE bowel cleansing regimens use sodium phosphate, which has raised safety concerns. Therefore, the aim of the current study was to test the feasibility and efficacy of a new low-volume, sodium phosphate-free polyethylene glycol (PEG) bowel preparation. Methods: The first 26 patients (original cleansing procedure) received a colon cleansing regimen of PEG plus ascorbic acid: patients drank 1 L in the evening and 0.75 L in the morning before capsule ingestion. Patients also drank an additional 0.5 L PEG boost and an optional 0.25 L PEG boost during the capsule procedure. Following an interim analysis, the cleansing procedure of the subsequent 24 patients was modified, with the morning intake before capsule ingestion being increased to 1 L, as well as the second boost (0.25 L) being administered 1 - 2 hours earlier (modified cleansing procedure). Results: The overall colon cleanliness was considered to be good or excellent in 83 % (original cleansing procedure) and 82 % (modified cleansing procedure) of patients, without any significant difference between regimens (P > 0.05). In 37 /49 (76 %) of the CCE procedures, the hemorrhoidal plexus was identified and thus the examination was considered complete, with no significant differences between the two CCE cleansing procedures. The capsule sensitivity and specificity for detecting colonic polyps ≥ 6 mm were 91 % (95 %CI 70 % - 98 %) and 94 % (95 %CI 87 % - 97 %), respectively, compared with standard optical colonoscopy. Conclusion: A colon cleansing procedure using PEG + ascorbic acid for capsule colonoscopy yielded an adequate cleansing level in > 80 % of patients, a completion rate of 76 %, and good accuracy for detecting polyps. This procedure may be considered as an alternative, particularly for patients in whom sodium phosphate-based preparations are contraindicated.
Gesehen am 30.10.2018